2011
DOI: 10.1128/cvi.05166-11
|View full text |Cite
|
Sign up to set email alerts
|

Immunochromatographic IgG/IgM Test for Rapid Diagnosis of Active Tuberculosis

Abstract: For rapid diagnosis and discrimination between active tuberculosis (TB) and other pulmonary diseases, we evaluated the clinical usefulness of detection of serum immunoglobulin IgG and IgM antibodies raised against mycobacterial 38-kDa, 16-kDa, and 6-kDa antigens by a commercial rapid immunochromatographic IgG/IgM test (Standard Diagnostics, South Korea) in 246 serum samples from three groups of patients: (i) 171 patients with active TB (128 with pulmonary TB [pTB] and 43 with extrapulmonary TB [epTB]), (ii) 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…identified 30 children as negative (true negative) and one child as positive (false positive). This result compatible with the study done in (Algeria) which revealed poor sensitivity and high specificity of ICT test; the sensitivities of ICT was (2.3%), while its specificity was 100% [12] . There was study done in Sudan by Ali compatible with our result which was very low about 2% the sensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…identified 30 children as negative (true negative) and one child as positive (false positive). This result compatible with the study done in (Algeria) which revealed poor sensitivity and high specificity of ICT test; the sensitivities of ICT was (2.3%), while its specificity was 100% [12] . There was study done in Sudan by Ali compatible with our result which was very low about 2% the sensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the reports showing significantly higher sensitivities of the IgG test compared with the IgM, IgA, or IgG/IgM tests in response to mycobacterial antigens (21,22), we aimed to evaluate the IgG responses to five different M. tuberculosis antigens, 38-kDa and 16-kDa antigens, ESAT-6, CFP-10, and lipoarabinomannan (LAM), in the sera of active TB patients, TB contacts with LTBI, and controls. We correlated antigen-specific IgG responses with infection state, TB recurrence, drug resistance, bacterial burden, M. tuberculosis genotype, and patient body mass index (BMI) and gender, in order to identify candidate antigens with clinical value for TB diagnosis and elucidate factors that may influence M. tuberculosis-specific IgG responses in TB patients.…”
mentioning
confidence: 99%
“…The use of antigens has shifted from purified proteins of mycobacterial culture to genetically engineered antigens. The currently used TB antigens include the 38-kDa protein (Silva et al, 2003;Ben-Selma et al, 2011), the 16-kDa protein (Senol et al, 2007;Ben-Selma et al, 2011), lipoarabinomannan, HspX, MTB48 (Lodes et al, 2001), and Mtb81 (Silva et al, 2003;Perkins et al, 2003;Ben-Selma et al, 2011). Despite significant research efforts, the sensitivity, specificity, sputum acid-fast bacilli-positive concordance rate, and relevance of a serious condition reveal little useful information.…”
Section: Discussionmentioning
confidence: 99%
“…However, the limitations of this method include its low sensitivity, multiple testing, and loss of manpower, among others (Steingart et al, 2006). Recently, serological methods for TB diagnosis have been applied, and early laboratory diagnosis of TB has achieved good results; however, several limitations remain (Zhu et al, 2004;Steingart et al, 2009;Ben-Selma et al, 2011). Identification of stable and efficient specific antigens or antigen combinations has been challenging.…”
Section: Introductionmentioning
confidence: 99%